Ipteks bagi Remaja Karang Taruna RT 10 RW 03 Kelurahan Kalipancur Kecamatan Ngaliyan Kota Semarang untuk Meningkatkan Kecakapan Menyimak dalam Bahasa Inggris - Rosyidi, Mohamad Ikhwan; Farida, Alief Noor (Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2020)
This community service aims at improving youth communityâ€™s (Karang Taruna) English proficiency in RT 10 RW 03 Kelurahan Kalipancur, Kecamatan Ngaliyan, Kota Semarang by giving training of English listening comprehension equal to TOEFLÂ® (Test of English as Foreign Language). It is done in order to make them able to communicate in English fluently in their daily life, instead of developing other forms of creativity. Method applied was workshop and communicative practice with English listening skill. Model of the service was direct face-to-face meeting between the service teams and the participant. Result shows that the participants present their English listening proficiency in form of evaluation. The evaluation presents that their listening proficiency has increased. Through this program, the participants gain knowledge and skill for fluent communication on listening spoken English and fill their days with their creativity and innovation on idea presentation.